Islamic Business Ethics: Practice of Buying and Selling Antibiotics Without a Doctor's Prescription - Dinda Putri Faridti; Nadia Dwi Oktaviani; Siti Baroroh Zakiyatul Islah; Muhammad Faqih; Mia Kusumawardani Samiyo (Solo International Collaboration and Publication of Social Sciences and Humanities, 2023)
Ethical dilemmas are associated with business, and identifying these ethical dilemmas is a key aspect of Islamic marketing strategy. In terms of terminology, business ethics is also called the science of good or bad behaviour regarding values. In simple terms, business ethics is an economic science that is often forgotten by society. Related to the existence of resistance due to irrational use of drugs, one of them is caused by use that is not by the patient's clinical conditions which occurs due to the use of antibiotics without a doctor's prescription. This occurs because it is easy for people to obtain antibiotics without considering or getting recommendations from authorized health workers, especially doctors (Ihsan et al., 2016). The purpose of this article is to explain Islamic ethics in business based on Islamic principles in health services when purchasing antibiotics without a doctor's prescription at pharmacies. The search method for scientific articles used as literature in this review is through the scientific journal article websites ScienceDirect, Scholar, Harzing Publish or Perish using the keywords "Islamic philosophical ethics"; “Islamic business ethics”; "antibiotics without a doctor's prescription". The importance of Islamic business ethics in antibiotic buying and selling transactions for patient health in using antibiotics appropriately to prevent antibiotic resistance and encouraging understanding of pharmacies to comply with health laws.